ENERGY COST AND OPTIMIZATION OF A CLOSED CIRCUIT CRUSHING PLANTWITH A CENTRIFUGAL CRUSHER - Elias Stamboliadis; Dimitris Stamboliadis (European Scientific Journal, ESJ, 2014)
A closed circuit crushing consists of a crusher that breaks the feed material, a screen that classifies the material and a conveyor system that returns the over size back to the crusher. The capacity of a centrifugal crusher with a given motor power depends on its rotation frequency. The lower the rotation frequency the lower the specific energy, or breakage intensity, that the particles obtain before breakage and hence the greater the capacity of the crusher to provide a low specific energy to the feed particles On the other hand, according to the breakage model the fraction of the feed that breaks below the feed size class is greater as the kinetic energy given to the particles increases. The combination of these two parameters has two effects: a) the energy cost per mass of the material broken by the crusher decreases as the breakage intensity decreases and b) the circulating load that has to be returned to the crusher increases as the breakage intensity decreases. This paper shows how to calculate the optimum crusher breakage intensity, or rotation frequency, in order to minimize the energy cost per ton of the product broken below size.